Asian Migrants and Religious Experience : From Missionary Journeys to Labor Mobility - Yeoh, Brenda S. A.; Brown, Bernardo E. (Book collections on Project MUSE., 2018)
Typically, scholars approach migrants' religions as a safeguard of cultural identity, something that connects migrants to their communities of origin. This ethnographic anthology challenges that position by reframing the religious experiences of migrants as a transformative force capable of refashioning narratives of displacement into journeys of spiritual awakening and missionary calling. These essays explore migrants' motivations in support of an argument that to travel inspires a search for new meaning in religion.